Neutrophil-to-lymphocyte ratio as a potential biomarker in predicting in-stent restenosis: A systematic review and meta-analysis. - Paulus Parholong Siahaan; Wynne Widiarti; Pandit Bagus Tri Saputra; Rendra Mahardhika Putra; Mario D'Oria (PLoS ONE)
Background In-stent restenosis (ISR) remains a significant challenge despite advancements in percutaneous interventions, often leading to adverse clinical outcomes. The neutrophil-to-lymphocyte ratio (NLR) has emerged as a potential biomarker for predicting ISR, offering opportunities for improved risk stratification and treatment personalization. This systematic review and meta-analysis assess the predictive value of NLR in ISR, providing insights into its clinical applicability. Methods Systematic literature search was conducted in scientific databases until 21st July 2024. Observational studies evaluating NLR in stented patients were included. Random effect meta-analysis and linear regression model were used to investigate odds ratios (OR) as predictor and linear dose-response relationship of ISR. Sensitivity and specificity of NLR to predict this outcome were pooled and a summary receiver operating characteristics (sROC) curve was generated. This study was already registered in the PROSPERO (ID: CRD42024555123). Results 15 studies with 3 889 patients were included. High NLR was associated with increased risk of ISR in coronary and non-coronary stenting [aOR = 1.61 (95%CI 1.14-2.25); aOR = 1.69 (95%CI 1.52-1.87)]. One unit increase of NLR is equal to 30% and 44% increased risk of ISR in coronary and non-coronary patients. Included studies showing NLR as a robust predictor of ISR with sensitivity and specificity of 70.5% (95%CI 60.1%-79.2%) and 74.1% (95%CI 56.7%-86.2%) for coronary stenting and 77.7% (95%CI 69.8%-84.0%) and 66.4% (95%CI 49.6%-79.8%) non-coronary stenting, with AUC of 0.77 (0.70-0.82) in the coronary and 0.79 (0.70-0.85) in the non-coronary sub-groups. Conclusion In conclusion, NLR yields promising predictive and prognostic potentials in predicting ISR in coronary and non-coronary stents. Additionally, NLR appears to be more proficient in predicting early ISR compared to late ISR in both coronary and non-coronary stents.